A novel method to determine the coupling scaling laws of vibration characteristics for rotor-bearing systems. (November 2021) - Zhang, Wendi; Luo, Zhong; Li, Yuqi; Zhu, Yunpeng
The purpose of this article is to study the coupling effects of support stiffness on geometric scaling factor powers of the rotor-bearing system and predict vibration characteristics of a prototype by scaled models accurately. Associated to the least-squares–based similitude method, the discrete iteration method proposed evaluates the estimated scaling laws under variable (instable) powers and further broadens the restriction of boundary conditions in scaling laws, which is the main finding in this article. The discrete iteration method does not need to establish a physical model but directly uses input and output parameters to establish output scaling laws. The complete scaled model and geometric distorted model are selected as study cases to prove the effectiveness and accuracy of the discrete iteration method. The vibration characteristics of the rotor-bearing system are obtained by the finite element method with validation by experimental test for the natural characteristics. The comparison between the prediction results and those without the discrete iteration method shows that discrete iteration method can significantly improve the accuracy for predicting the prototype.